Older Adult Caregivers' Experiences in an Online, Interactive Mindfulness Intervention - Janella Hudson PhD; Rachel Ungar MPH; Laurie Albright MSW; Rifky Tkatch PhD; James Schaeffer RPh; Ellen R. Wicker MHA (SAGE Publishing, 2020)
Background. While today's older adults experience longevity, they often manage several chronic conditions and increasingly serve as informal caregivers for aging parents, children with life-long disabilities, and spouses. Older adult caregivers managing personal chronic illness often experience significant psychosocial hardships. Objective. The primary purpose of this study was to explore the experiences of older adult caregivers in an online, interactive mindfulness intervention. Methods. Self-reported older caregivers who participated in an online-based mindfulness program (n = 20) were recruited for semi-structured interviews. Participants were asked to provide feedback about any previous experience with mindfulness and/or meditation, hopes or goals held prior to the start of the program, desired expectations, motivation for joining, impressions of sessions, most beneficial topics, potential application of content, and any perceived effects. Participants' responses were analyzed using qualitative content analysis. Results. Five themes emerged from the analysis: Managing the Comprehensive Effects of Caregiving, Openness to Meditation and Mindfulness, Course Engagement and Incremental Growth, Building Rapport through Shared Experiences, and Ongoing Application and Opportunities for Refinement. Participants reported both short-term post-exercise benefits such as increased calm, relaxation, and stress relief, as well as long-term positive outcomes. Notably, participants found the program's unique interactive feature to be particularly beneficial as a form of perceived social support. Conclusions. Caregivers for older adults may derive benefit and potentially experience reduced subjective caregiver burden as a result of participating in a Mindfulness-Based Stress Reduction (MBSR) program, particularly when the program is augmented with a self-compassion approach and perceived social support.